The Ethical Deviations of AI in Marketing Practices: A Critical Review from Halal Perspectives - Koswara, Asep; Herlina, Lina (SAN Scientific, 2025)
This paper critically examines the ethical deviations in Artificial Intelligence (AI) tools used for marketing practices from a halal perspective, focusing on Islamic ethical principles. The research highlights risks associated with AI technologies like generative AI (e.g., ChatGPT), image generators, face-swapping tools, and voice cloning, which can lead to misinformation, manipulation, and exploitation. These issues contradict Islamic values of justice (‘adl), integrity (amanah), and harm avoidance (mafsadah). Using a qualitative, exploratory approach, this study identifies key ethical violations while introducing the novel concept of integrating halal principles into AI governance frameworks for marketing. The managerial implications of this research include the necessity for businesses to adopt ethical guidelines, conduct regular AI audits, and prioritize consumer trust through transparent and accountable practices. Companies can enhance competitive advantage by aligning their AI-driven marketing strategies with halal standards, fostering trust among diverse consumer bases. This study not only addresses immediate ethical concerns but also lays the foundation for developing AI tools aligned with Islamic values, contributing to responsible innovation and long-term societal impact.